Towards a critical geography of resettlement - Rogers, Sarah; Wilmsen, Brooke (Progress in human geography, 2020)
Resettlement is a governmental program with inherent spatial effects in that it drives the rearrangement of capital, labour, and land, and seeks to render people and space more governable. This article examines the extent to which this disruptive phenomenon has been theorised. We first review the existing literature, finding a distinct polarisation between mainstream studies and more critical scholarship. We then propose a critical geography of resettlement centred on its multiple logics, agents and expertise, and subject-making and spatial practices. An invigorated critical geography of resettlement is needed to challenge the legitimisation of an expanding resettlement industry.